From the question If a is the eigenvalue of A, then a is also the eigenvalue of AT where T means transpose.
Proof (I've tried answering it not sure if I am right)
If Ax=ax by definition
=> (AT-aIT)x=0 (since a is just a scalar from the properties of the transpose (aA)T=aAT and IT=I
Thus, ATx=ax. completes the proof!
- 1 decade agoFavorite Answer
seems correct to me
- I know some mathLv 41 decade ago
Although I don't like to use the notation T for transpose,
I will just stick to the notation (I would use "^t" as in A^t).
Let us look at the following arguments you had:
(A - aI)x = 0 => (A - aI)Tx = 0T.
To go from LHS to RHS, I think that you transpose the
both sides, but the transpose of (A - aI)x is not (A - aI)Tx.
Why? In general, (AB)T is not ATBT. In general, (AB)T
Now do you see how you can fix the proof?
*** Addendum ***
Let me add few more lines since some people seem confused.
When the questioner deduced (A - aI)Tx = 0T (3rd line from the
deductions) from the second line (A - aI)x = 0, the questioner
was trying to transpose the left hand side and the right hand
side. However, the transpose of (A - aI)x is not (A - aI)Tx as
the questioner wrongfully concluded. Let M = A - aI and N = x
be two matrices, then as I explained above (MN)T = NTMT,
so the traspose of (A - aI)x is xT(A - aI)T, which is a different
matrix from (A - aI)Tx.
Here is a proof of the assertion that the questioner wanted
Proof: Let A be a matrix with an eigenvalue a. Then the
determinant of the matrix A - aI is zero, i.e. det(A - aI) = 0.
We know that the determinant is transpose invariant, i.e.
det(C) = det(C^t) (here C^t means the transpose of C).
Thus, det(A - aI) = det((A - aI)^t). On the other hand,
(A - aI)^t = A^t - aI^t = A^t - aI (as two commentators remembered).
Thus, det(A^t - aI) = det(A - aI) = 0. Hence, a is also an
eigenvalue of A^t, the transpose of the matrix A. QED
- 1 decade ago
Puggy is absolutely correct. The property of transpose on addition or subtraction is distrubitve!
Why that someone would impose the property of transpose on a matrix multiplication beats me unless they were half asleep writing this.
- PuggyLv 71 decade ago
It looks correct to me as well. I noticed you used the property that
(A + B)^T = A^T + B^T
And this is absolutely correct. What confuses me is how someone claimed you used the property
(AB)^T = (B^T)(A^T)
which you didn't, because you're taking the transpose of two matrices being subtracted (which is a special form of adding).
- How do you think about the answers? You can sign in to vote the answer.
- Anonymous1 decade ago
what is aI in 2nd step?